Knowledge mapping of Computational Thinking and Science, Technology, Engineering, and Mathematics (CT+STEM) - Supriyadi, Edi; Taban, Joseph Gacusan (Universitas Terbuka, 2024)
Despite growing interest in Computational Thinking (CT) integration within STEM education, significant gaps remain—particularly regarding underrepresented college students, CT inclusion at the entry level, and limited teacher preparation for CT integration. This study addresses these gaps by examining how educators’ professional experiences influence their attitudes and practices related to CT in STEM contexts. It also underscores the urgent need for empirical evidence to navigate the tension between generalized critical thinking frameworks and the unique demands of scientific representations in instructional planning. To map the development and current landscape of CT+STEM research, a bibliometric analysis was conducted on literature published between 1978 and 2023. The analysis reveals a consistent annual growth rate of 7.22% in the CT+STEM domain, encompassing 241 publications across 127 scholarly sources. The study identifies key authors, institutions, and influential works, while also visualizing global collaboration patterns and thematic trends in the field. This research contributes to the advancement of CT+STEM by providing a comprehensive overview of its evolution, highlighting areas of strength and underexplored dimensions. Although the study is quantitative in nature and acknowledges limitations such as potential database bias, it lays a foundation for future inquiry into qualitative methodologies, pedagogical strategies, and inclusive practices. The findings hold significant implications for educational policy, workforce development, and digital-age problem-solving, and call for deeper exploration into the pedagogical and sociocultural dynamics that shape effective CT+STEM integration.